Current Advances on 3D‐Bioprinted Liver Tissue Models. Issue 24 (19th October 2020) - Ma, Liang; Wu, Yutong; Li, Yuting; Aazmi, Abdellah; Zhou, Hongzhao; Zhang, Bin; Yang, Huayong
Abstract: The liver, the largest gland in the human body, plays a key role in metabolism, bile production, detoxification, and water and electrolyte regulation. The toxins or drugs that the gastrointestinal system absorbs reach the liver first before entering the bloodstream. Liver disease is one of the leading causes of death worldwide. Therefore, an in vitro liver tissue model that reproduces the main functions of the liver can be a reliable platform for investigating liver diseases and developing new drugs. In addition, the limitations in traditional, planar monolayer cell cultures and animal tests for evaluating the toxicity and efficacy of drug candidates can be overcome. Currently, the newly emerging 3D bioprinting technologies have the ability to construct in vitro liver tissue models both in static scaffolds and dynamic liver‐on‐chip manners. This review mainly focuses on the construction and applications of liver tissue models based on 3D bioprinting. Special attention is given to 3D bioprinting strategies and bioinks for constructing liver tissue models including the cell sources and hydrogel selection. In addition, the main advantages and limitations and the major challenges and future perspectives are discussed, paving the way for the next generation of in vitro liver tissue models. Abstract : Currently, newly emerging 3D bioprinting technologies have the ability to construct in vitro liver tissue models both in static scaffolds and dynamic liver‐on‐chip manners. Cells from the liver are mixed with hydrogels as bioinks for 3D bioprinting. The printed liver tissue models can be applied in liver regeneration or new drug development.